Analysis of Motivation Factors and Employee Performance: The Role of Work Environment, Compensation, Career, and Self-Actualization - Indriati Amirullah; Nurasia Natsir (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze the factors affecting employee performance and provide recommendations to enhance it. The findings of this research are expected to contribute significantly to improving the efficiency and effectiveness of the organization. This research adopts a quantitative approach and uses a survey method as the research design. The aim of this study is to identify and analyze the influence of motivation factors such as work environment, compensation, career development, and self-actualization on employee performance. The research is conducted by collecting data from respondents who are employees in various organizations and companies in Makassar Employee performance is a critical element within an organization. Performance refers to the work outcomes or achievements accomplished by an employee. In this context, performance encompasses various indicators, including work motivation and employee behavior. However, initial observations suggest that employee performance, whether influenced by internal factors such as education and motivation, or external factors like experience and interactions, still tends to be relatively low. This subjectively impacts company management, especially in task execution and organizational functions.